(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This paper showcases the Role of an NGO in Inclusive entrepreneurship in India - A case Study of BYST. The use of the word ’inclusive’ indicates a belief that entrepreneurship is for all and that the personal qualities and conditions required for entrepreneurship are not the prerogative of a privileged, highly educated few. NGO play a major role in the promotion and development of the society. They play the service role, help to increase community participation , women empowerment and achieving the sustainable goals.